MENINGKATKAN KOMPETENSI GURU KIMIA DALAM PENGGELOLAAN KELAS MELALUI KEGIATAN MGMP DI KOTA LHOKSEUMAWE TAHUN PELAJARAN 2015/2016 - Fitriani Fitriani (JURNAL TEMATIK, 2015)
problems in school action research is experienced by both teachers as teachers beginners and experienced is classroom management. As a professional educator, teachers are required not only carry out the task of educating and teaching, but also had to develop the profession. But the facts show that teachers, especially teachers of chemistry in the town of Lhokseumawe is still much less able to manage the class well, this is indicated by the presence of students who talked in class when learning activities are running, of course this situation is not desirable by any because when the teacher educators (teachers) carry out the teaching and learning activities are not able to manage the class and do not understand the characteristics of students with both the student achievement Yangdi not running as expected. The purpose of this research is to improve the chemistry teacher competence in classroom management through MGMP. To achieve these objectives, the method used in this activity is the training of the teachers of chemistry in the city of Lhokseumawe